The clay lamps from ancient Sepphoris : light use and regional interactions - Lapp, Eric C. (Sepphoris excavation reports, 2016)
"Sepphoris was an important Galilean site from Hellenistic to early Islamic times. This multicultural city is described by Flavius Josephus as the 'ornament of all Galilee,' and Rabbi Judah the Prince (ha-Nasi) codified the Mishnah there around 200 CE. The Duke University excavations of the 1980s and 1990s uncovered a large corpus of clay oil lamps in the domestic area of the western summit, and this volume presents these vessels. Richly illustrated with photos and drawings, it describes the various shape-types and includes a detailed catalog of 219 lamps. The volume also explores the origins of the Sepphoris lamps and establishes patterns of their trade, transport, and sale in the lower city's marketplace. A unique contribution is the use of a combined petrographic and direct current plasma-optical emission spectrometric (dcp-oes) analysis of selected lamp fabrics from sites in Israel and Jordan. This process provided valuable information, indicating that lamps found in Sepphoris came from Judea, the Decapolis, and even Greece, suggesting an urban community fully engaged with other regional centers. Lamp decorations also provide information about the cosmopolitan culture of Sepphoris in antiquity. Discus lamps with erotic scenes and mythological characters suggest Greco-Roman influences, and menorahs portrayed on lamps indicate a vibrant Jewish identity"--Provided by publisher.